PROTOTYPE ALAT PENDETEKSI LOKASI PADA LANSIA DAN ORANG PIKUN BERBASIS INTERNET OF THINGS (IoT) DI WILAYAH KAMPUNG PAMAHAN BEKASI - Aswan Supriyadi Sunge (Jurnal Pelita Teknologi, 2022)
Parents (elderly) have such physical limitations as vision impairment, walking ability, and hearing. And for the senile it takes time to remember or forget what was done before. Parents and the senile are often abandoned by their children and their families for reasons of work. One of the problems faced by parents, relatives and family is the inability to know their whereabouts and condition outside the home. This makes it difficult for loved ones and families to discover the whereabouts of their parents. This tool uses the Internet of Things with Android apps that can be accessed online through the user familys own smartphone. Using the main component of the U-BLOX NEO-6M module and MIT App Inventor 2. GPS will help provide information on outdoor locations and is expected to help provide information on the where abouts and circumstances of parents (elderly) and senile people when they get lost.